MOTIVATION IN READING ENGLISH JOURNAL ARTICLES AMONG STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Eko Kurniawan (FPB PBI 16 UMY 010, 2016)
Reading English journal article is the process to transfer some ideas to students’ brainstorming on the journal articles. In reading English journal articles, it is related with students’ motivation because motivation is the most important factor to drive the individuals to get goal and desire that students want to achieve. Many of students of English Education Department of Universitas Muhammadiyah Yogyakarta felt bored in reading English journal articles. Therefore, this research is to find out the kinds of motivation in reading English journal articles among students of English Education Department (EED) of Universitas Muhammadiyah Yogyakarta (UMY). In addition, this research is to find out the advantages of students of EED of UMY got in reading English journal articles. Furthermore, the methodology in this research is descriptive qualitative. The setting of the research is in EED of UMY, and also there are three respondents from the students of EED of UMY batch 2011 who have been interviewed. The results showed that the students’ motivation of EED of UMY in reading English journal articles is influenced by two kinds of motivation; intrinsic motivation and extrinsic motivation. In addition, there are some advantages of students of EED of UMY get by reading English journal articles; improving students’ vocabulary, students’ grammar and students’ critical thinking.